Efect of Antioxydants on Viscosity and Breakdown Voltage of Palm Oil Insulation - Ronald A Sitorus; Yenni Afrida; Herman H Sinaga; Dewi A Irayani; Nining Purwasih; Diah Permata (Journal of Renewable Energy, Electrical, and Computer Engineering, 2024)
Insulating oil is a type of insulator that is widely used as insulation in electrical equipment such as transformers. The insulating oil in the transformer functions as insulation in the transformer windings so that flashover does not occur and causes voltage leaks to the outside of the transformer, then the insulating oil also functions as a transformer coolant. Generally, the insulating oil used today is made from mineral oil which cannot be renewed so its availability is limited and may run out in the future. In an effort to reduce the use of mineral oil as a basic ingredient for insulating oil, it is necessary to develop a basic ingredient for making insulating oil, which can use vegetable oils such as crude palm oil (CPO) with the additive butylated hydroxytoulene added. In testing the suitability of crude palm oil with the addition of butylated hydroxytoulene additive as insulating oil, breakdown voltage testing was carried out using Megger OTS80Af and viscosity. Based on the test results, the highest breakdown voltage value was obtained for crude palm oil with the addition of butylated hydroxytoulene of 11.13 kV and a viscosity of 27.12 cSt. From the test results, it can be concluded that crude palm oil with the addition of butylated hydroxytoulene is not suitable for use as transformer insulating oil because it cannot meet the standard SPLN 49-91: 1982, the breakdown voltage of transformer insulating oil is 30 kV/2.5 mm.